Pengaruh Kepribadian Big-Five dan Minat Karier Terhadap Pengambilan Keputusan Karier Siswa - Qurr'aeni, Nabilla Putri; Pravesti, Cindy Asli (Institut Agama Islam Negeri Curup, 2025)
Personality can help a person understand their strengths and weaknesses, this will allow them to decide how they interact with others. Meanwhile, interests can be an internal factor that can influence a person in taking steps in determining a career. The fact is, there are still many students who do not understand their personality characteristics and interests, making it difficult to determine career choices appropriately. This study aims to examine the influence of students' personality and interests in the career decision-making process. This study is quantitative. A total of 165 active students of class X SMA Dr. Soetomo Surabaya were the samples in this study. This study uses a Likert Scale and questionnaires distributed via the Google Form link. For the data analysis, we employed descriptive analysis alongside multiple regression, equipped to conduct prerequisite tests including normality, heteroscedasticity, and multicollinearity assesments. The results of this study indicate that the most data was obtained on the personality aspect with a percentage of 73.9%, followed by career interests at 75.7%, and career decision making reached 77.5%. These three aspects are categorized as “moderate” and produce a correlation value between big-five personality and career interest that is positive and significant contributing 51.4% to the career decision-making of grade X students of SMA Dr. Soetomo Surabaya. This means that the higher the level of students’ understanding of their personality and interests, the better their understanding in making career decisions.